Functional characteristics of hydroxyapatite sintered at high temperatures - К.I. Сокол; Р.В. Вовк (Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ: fìzika.)
The functional characteristics of hydroxyapatite, which has carbonate impurities inside the hydroxyapatite crystal lattice after sintering in the temperature interval from room temperature  to 1400°C have been studied. It has been shown, that carbonate impurities are present in hydroxyapatite up to 1000°C. Hydroxyapatite has a mixed AB - type of carbonate substitution. It has been shown, that all samples after the heating and sintering in the temperature interval from room to 1400°C contain single phase hydroxyapatite. The samples have density greater than 95% of the theoretical for hydroxyapatite at the temperature of 1200°C. The active shrinkage of the samples starts at temperature near 700°C and reaches the maximum value at 1280°C. The same tendency was demonstrated by the dependence of Vickers microhardness on sintered temperature. The maximum Vickers microhardness of 5.5 GPa was obtained in this work on the samples of hydroxyapatite after sintering at the temperature of 1100°C. The mechanisms of the hydroxyapatite sintering at 1150°C have been studied. It has been shown, that the diffusion during the sintering of the samples is realized by the surface diffusion mechanism, as well as through the interface grain boundaries in the polycrystalline hydroxyapatite. The microstructure of the hydroxyapatite particles after heating at high temperatures was studied. It has been shown, that at the initial stage of the sintering of hydroxyapatite, active mass transfer take place, which at the temperature of 1000°C leads to the sintering of the particles with neck formations between them. The Arenerus plot of the size of hydroxyapatite particles as a function of the heating temperature was obtained. The activation energy for diffusion processes in the particles at different temperatures was calculated. The obtained values were 36, 83, 5.11 and 11.28 kcal/mol at different intervals for the heating of hydroxyapatite.